Micrometre Scale Performances of Industrial Robot Manipulators - Diala Dandash; Jean-François Brethé; Eric Vasselin; Dimitri Lefebvre (International Journal of Advanced Robotic Systems, 2012)
Robot precision is usually characterized by repeatability and accuracy. In this paper, we show that these indices are not sufficient to describe robot behaviour at the micrometre scale. New, precision performances are discussed and the experimental procedure to estimate these indices is described. The main results of the experimental work performed on Samsung Faraman and Epson Scara robots are displayed. Reversibility, hysteresis and spatial resolution have to be taken into account when the robot has to be controlled precisely at the micrometre scale. A granular control design including harmonization poses is proposed as a conclusion.